Hubungan Antara Perhatian Orang Tua Dengan Prestasi Belajar Siswa MI Al- Asy’ariyah Banjarsari Bandarkedungmulyo Jombang Tahun Pelajaran 2015/2016 - Mashuriyati; Dian Triana; Atim S (FAI- Undar, 2018)
Attention that is psychical energy concentration concentrated to an object. And Achievement learn to represent the assessment of result of activity learn expressed in the form of number, letter and also sentence mirroring is reached by the result of protege in specified period. In order to increase achievement learn the child, parent role cannot be discharged off hand, because that matter represent one of effort to guide all potency and resource exist in child. Hence parent requires giving the special attention to learning child. As for target which wish in reaching is to know there is or do not it him relation of between parent attention with the achievement learn the student of Al Asy’ariyah Banjarsari Bandarkedugmulyo Jombang pada Tahun Ajaran 2015/2016. In this research in for becoming two shares, first shares about theory study, second shares about empirical study. Theory study represent the solution of through bibliography study, while empirical study obtained from data by using observation method, interview, questioner and documentation. While determination sample technically is random sampling From obtained data, hypothesis in test by using formula of coefficient of product moment From research result, after data analyzed is hence obtained by a conclusion there is relation of between parent attention with the achievement learn the student of Al Asy’ariyah Banjarsari Bandarkedugmulyo Jombang pada Tahun Ajaran 2015/2016.